ALTERNATIF PENYELESAIAN SENGKETA DI PASAR MODAL INDONESIA: ANALISIS SISTEM HUKUM DAN REKONSTRUKSI MENUJU KEADILAN EFISIEN - Martien, Dhoni; Guritno, Yulianto (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
An effective dispute resolution is a fundamental pillar for investor confidence and capital market stability. This study critically examines the dispute resolution system in the Indonesian capital market following its integration into the Alternative Dispute Resolution Institution for the Financial Services Sector (LAPS SJK). This research employs a normative juridical method using Lawrence M. Friedman's legal system theory as an analytical tool to dissect the current state (das sein) and Roscoe Pound's theory of law as a tool of social engineering to formulate an ideal model (das sollen). The first research question analyzes the effectiveness and problems of LAPS SJK, highlighting the paradoxical impact of Constitutional Court Decision No. 15/PUU-XII/2014. This decision, while intended to remove procedural hurdles, has inadvertently facilitated the filing of annulment of arbitral awards and eroded the principle of finality. The second research question formulates a reconstruction of the ADR mechanism in the capital market by leveraging the momentum of Law No. 4 of 2023 on Financial Sector Development and Strengthening (PPSK Law) to mitigate the negative impacts of the said Constitutional Court decision. The findings indicate that the current system experiences dysfunction due to inconsistencies between the altered legal substance, a judicial structure that remains the final destination, and a litigation-oriented legal culture. Therefore, it is recommended to engineer the law through the Financial Services Authority (OJK) to redefine the grounds for annulment in technical regulations, optimize Online Dispute Resolution (ODR), and align the legal culture of capital market actors.